(untitled) (Fiep Bulletin - online, 2014)
The challenges at the beginning of a new century have led several authors to interpretations of contemporary days: Eric Hobsbawm, Perruchon de Bouchard, Alvin Toffler, Edgar Morin, Gilles Lipovetsky, Guy Debord and several others. What all these interpretations have in common is the acknowledgement that our present world is under the decisive influence of the advances of communication means – also, that the consensus has been replaced by dissension – generating new concepts in all areas of knowledge. Physical Education has had its new concept revised by the World Manifesto of Physical Education – FIEP 2000. In this new concept, the delimitation of Physical Education is not childhood and adolescence, but it is rather an educational process which grows throughout the individual’s life: in other words, it became physical education for children, adolescents, youths, adults and elderly. Physical education, based on person’s rights to Physical Education for the sake of an Active Life Style, has defined human development as one of its goals. In such a process, Education for a Health and for Leisure became a priority. According to this new interpretation, Physical Education is seen as teaching for the acquisition of motor abilities, attitudes and knowledge. This renewed concept of Physical Education, besides providing a new sense to its programs, eliminates its old approach of simple activities, entertainment or fad.